2019
DOI: 10.1364/ol.44.003410
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based pulse characterization in figure-eight mode-locked lasers

Abstract: By combining machine learning methods and the dispersive Fourier transform we demonstrate, to the best of our knowledge, for the first time a possibility to determine the temporal duration of picosecond-scale laser pulses using nanosecond photodetector. A fiber figure of eight (F-8) laser with two amplifiers in a resonator was used to generate pulses with duration varying from 28 to 160 ps and spectral width varied in the range of 0.75 to 12 nm. Average power of the pulses was in range from 40 to 300 mW. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…[9,10] In laser optics, AI techniques substantially enhance the automatic optimization of mode-locked lasers [11][12][13][14][15][16][17][18][19][20][21] and the deep learning-based pulse characterization reveals outstanding robustness against noise. [22,23] The modulation instabilities in optical fiber are analyzed by a fully-connected neural network [24] and precise phase retrieval in the interferometric fringe patterns is also achieved by AI models. [25,26] On the other hand, with GPU-enabled compute unified device architecture (CUDA), the feed-forward computation of AI models can be substantially accelerated by parallel computing.…”
Section: Doi: 101002/lpor202200363mentioning
confidence: 99%
“…[9,10] In laser optics, AI techniques substantially enhance the automatic optimization of mode-locked lasers [11][12][13][14][15][16][17][18][19][20][21] and the deep learning-based pulse characterization reveals outstanding robustness against noise. [22,23] The modulation instabilities in optical fiber are analyzed by a fully-connected neural network [24] and precise phase retrieval in the interferometric fringe patterns is also achieved by AI models. [25,26] On the other hand, with GPU-enabled compute unified device architecture (CUDA), the feed-forward computation of AI models can be substantially accelerated by parallel computing.…”
Section: Doi: 101002/lpor202200363mentioning
confidence: 99%
“…One research in the fiber laser field showed temporal duration characterization of the mode-locked pulses using the dispersive Fourier transform trace [115]. The trained artificial neural network can predict the pulse duration with an average consistency of 95%.…”
Section: Ultrashort Pulses Reconstructionmentioning
confidence: 99%
“…Ultrafast lasers are also stochastic systems and the impact of noise can generally be only reproduced via computationally intensive Monte-Carlo simulations that require the analysis of a very large amount of data. One can anticipate that the use of machine learning techniques for pattern recognition combined with the latest advances in real-time measurement techniques [40,41] could lead to better understanding of ultrafast laser dynamics, allowing for the construction of laser systems with improved robustness.…”
Section: Self-tuning Of Ultrafast Fibre Lasersmentioning
confidence: 99%